Contribuições do Campus Universitário - UFPA e do Instituto Federal de Educação, Ciência e Tecnologia - IFPA para o desenvolvimento local no município de Bragança (PA) a partir do modelo da Hélice Tríplice - SOARES, Patrícia da Trindade (Universidade Federal do Pará, 2025)
The dissertation analyzed the contributions of the University Campus - UFPA and the Federal Institute of Education, Science and Technology - IFPA to the promotion of local development in the municipality of Bragança (PA) from the Triple Helix model. The study, aimed at analyzing the economic and social dimensions, was structured on quantitative data that show the performance of these HEIs in the generation of knowledge, innovative ideas and patent filing. The investigation focused on official data from government agencies for the period, predominantly, from 2014 to 2024. Additionally, information was collected about the intellectual production generated by research professors from UFPA and IFPA in the city, as well as about the partnerships made by them with organizations representing other propellers. Also added to the scope of this work, searches in the field of academic training of individuals who are part of the spheres of university, industry and municipal public governance. The research concluded that the educational institutions investigated are still in an incipient phase in the process of IFES – INDUSTRY – GOVERNMENT interaction. However, the participation of the educational units has increased over the last few years in articulations and actions aimed at strengthening entrepreneurship, the surrounding productive sectors and social issues in the community.